Policy Diffusion through Elections - Hitoshi Shigeoka; Yasutora Watanabe (Institute of Labor Economics (IZA), 2023)
Staggered difference-in-differences designs are pervasive in policy evaluations but little is known about the mechanisms of policy diffusion: How and why do such policies spread across jurisdictions? In this study, we highlight the role of elections in policy diffusion in settings where municipal elections are asynchronous due to historical reasons. First, we empirically show the presence of policy diffusion using neighbors' election cycles as instruments for neighbors' policy adoption. Second, we further demonstrate interactions of municipalities' election cycles with neighbors' adoption and show that they follow neighbors' policy only during their own election timing, indicating that policy diffuses through elections.
Keywords: D04; D78; H73; H75; 330; policy diffusion; elections; subsidy; child healthcare; political budget cycles